Body mass index and physical activity in relation to the incidence of hip fracture in postmenopausal women. - Armstrong, M; Spencer, E; Cairns, B; Banks, E; Pirie, K; Green, J; Wright, F; Reeves, G; Beral, V (2011)
Hip fracture risk is known to increase with physical inactivity and decrease with obesity, but there is little information on their combined effects. We report on the separate and combined effects of body mass index (BMI) and physical activity on hospital admissions for hip fracture among postmenopausal women in a large prospective UK study. Baseline information on body size, physical activity, and other relevant factors was collected in 1996-2001, and participants were followed for incident hip fractures by record linkage to National Health Service (NHS) hospital admission data. Cox regression was used to calculate adjusted relative risks of hip fracture. Among 925,345 postmenopausal women followed for an average of 6.2 years, 2582 were admitted to hospital with an incident hip fracture. Hip fracture risk increased with decreasing BMI: Compared with obese women (BMI of 30+ kg/m(2) ), relative risks were 1.71 [95% confidence interval (CI) 1.47-1.97)] for BMI of 25.0 to 29.9 kg/m(2) and 2.55 (95% CI 2.22-2.94) for BMI of 20.0 to 24.9 kg/m(2). The increase in fracture risk per unit decrease in BMI was significantly greater among lean women than among overweight women (p < .001). For women in every category of BMI, physical inactivity was associated with an increased risk of hip fracture. There was no significant interaction between the relative effects of BMI and physical activity. For women who reported that they took any exercise versus no exercise, the adjusted relative risk of hip fracture was 0.68 (95% CI 0.62-0.75), with similar results for strenuous exercise. In this large cohort of postmenopausal women, BMI and physical activity had independent effects on hip fracture risk.